Effect of Security Challenges on Water Accessibility in the Lake Basin Area - Mbusube, Zainab Modu; Yilwanu, Tasiu Yalwa; Gaya, Ibrahim Faruk ` (Department of Geography Education, University of Jember, 2026)
Lake Chad Basin (LCB) terrain has long been a lifeline for a large number of people who rely on it for agriculture, fishing, and livestock production. However, its water resources have come under severe stress due to a combination of climate variability, environmental degradation, and persistent insecurity driven by the Boko Haram insurgency and related conflicts. This study examines the effect of security challenges on water accessibility within the portion of the LCB. Using a mixed-methods approach that combined questionnaire surveys, focus group discussions (FGDs), and key informant interviews (KIIs), the research assessed the extent to which insecurity, insurgent activities, and environmental factors disrupt water availability, access, and infrastructure. Findings reveal that insecurity significantly limits community access to water points, disrupts agricultural activities, and contributes to displacement, thereby heightening food and livelihood insecurity. Moreover, insurgent attacks have destroyed water infrastructure, restricted transhumance flows, and forced communities to abandon traditional water-use practices. While some adaptive strategies exist, they remain insufficient, costly, and unsustainable. The study concludes that without integrating water management with peacebuilding, infrastructure protection, and community resilience strategies, achieving sustainable water accessibility in the LCB will remain elusive